Detection of apoptosis in human macrophage cell line, THP-1 infected with BCG and recombinant BCG (rBCG) expressing the 19-kDa C-terminus of the Merozoite Surface Protein-1 (MSP-1C) - Mei, Cheong Siew (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Malaria is a major cause of disease and death in tropical countries. With the spread of insecticide-resistant mosquito vector and increase in the prevalence of resistant parasite to anti-malarial drugs, there is an urgent need to develop an effective vaccine to control malaria infection. By utilizing Mycobacterium bovis BCG as a delivery system, a recombinant BCG vaccine expressing the 19 kDa MSP-1C of P. falciparum was constructed previously by assembly PCR. This vaccine candidate has been known to be capable of stimulating humoral immune response in mice and induce activation of mouse macrophage cell line in vitro. However, the effect of the rBCG vaccine on macrophage apoptosis, an important mechanism for parasite clearance has not been determined. Thus, the objective of this study was to determine the apoptosis activity of human macrophage cell line THP-1 infected with the rBCG clone. The apoptosis of untreated macrophage, macrophage infected with BCG and macrophage stimulated with LPS were used as controls. Expression of caspase 9 was also determined in order to identify the pathway involved in the apoptosis activity. The results demonstrated that macrophage apoptosis would be detected in all macrophage culture conditions. However, the apoptosis activity macrophages and LPS-stimulated macrophages. In addition, ELISA analysis also showed that caspase 9 activity was increased in rBCG infected macrophages compare to those of BCG and LPS stimulated macrophages. In conclusion, these data demonstrated that the presence of MSP-1C in rBCG increased macrophage apoptotic activity and the expression of caspase 9 in the infected macrophages. Thus, the rBCG candidate vaccine is potential to be used to control malaria infection in the future